Managing Potential Tax Risks and Compliance - Tichar Tambunan (Jurnal Riset Perpajakan: Amnesty, 2022)
Fulfillment of tax obligations in Indonesia adheres to a self-assessment system, which means calculating, depositing, and reporting the tax payable which will be carried out by the taxpayer himself. Although the government has given confidence to taxpayers with a self-assessment system, supervision must still be carried out to ensure the fulfillment of tax provisions. Managing potential tax risks and requests for information is important to respond to the applicable provisions in this case through the Circular Letter of the Director General of Taxes Number SE-05/PJ/2022 concerning Taxpayer Compliance Supervision. A tax payer's strategy is needed in responding to SP2DK by conducting a tax assurance review in order to be ready to face the Letter of Request for Explanation of Data and/or Information (SP2DK) from the authorities. Through tax assurance review, taxpayers can identify their own non-compliance risk based on how the authorities work in determining the risk profile of a taxpayer.